Of Gods and games: religious faith and modern sports - Baker, William J. (George H. Shriver lecture series in religion in American history, 2016)
Cover -- Half Title -- Title -- Copyright -- Contents -- Preface -- Prologue -- 1. Playing the God Game: A Tale of Two Christian Athletes -- 2. Beyond the Scoreboard: Coaches Tackling Some Tough Issues -- 3. Scribes and Sportscasters: Prophetic Voices from the Press Box -- A Concluding Postscript -- Sources -- Index